2023
DOI: 10.1111/apt.17406
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: Safety, tolerability, pharmacodynamics and pharmacokinetics of zastaprazan (JP‐1366), a novel potassium‐competitive acid blocker, in healthy subjects

Abstract: Background: Zastaprazan (JP-1366) is a novel potassium-competitive acid blocker with favourable preclinical safety and efficacy profile being developed for the treatment of acid-related diseases. Aims:To investigate the safety, tolerability, pharmacodynamics and pharmacokinetics of zastaprazan. Methods:A randomised, open-label, placebo-and active-controlled, single and multiple ascending dose clinical trial was conducted in healthy Korean male subjects. Intragatric pH and serum gastrin were measured to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Acid‐reducing agents, such as P‐CABs and PPIs, have a clear exposure–response relationship 17,22,30 . Similarly, in this study, we observed a clear exposure–response relationship for the gastric pH parameter following the administration of various combinatorial formulations of tegoprazan (Figure S2).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Acid‐reducing agents, such as P‐CABs and PPIs, have a clear exposure–response relationship 17,22,30 . Similarly, in this study, we observed a clear exposure–response relationship for the gastric pH parameter following the administration of various combinatorial formulations of tegoprazan (Figure S2).…”
Section: Discussionsupporting
confidence: 79%
“…Acid-reducing agents, such as P-CABs and PPIs, have a clear exposure-response relationship. 17,22,30 Similarly, in this study, we observed a clear exposure-response relationship for the gastric pH parameter following the administration of various combinatorial formulations of tegoprazan (Figure S2). Thus, it is suggested that maintaining long-term systemic exposure of tegoprazan is an essential prerequisite for achieving sufficient efficacy in preventing NAB.…”
Section: Discussionsupporting
confidence: 78%
“…However, a recent study showed that the pharmacokinetics and pharmacodynamics of fexuprazan were similar in healthy participants of different ethnicities (Korean, Japanese, and Caucasian). 23 Therefore, fexuprazan would have similar efficacy in people of other ethnicities. Second, to investigate the effect of fexuprazan, we included the following endoscopic findings of gastritis: erosion, edema, redness, and hemorrhage, with erosion as the main endoscopic finding analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In our publication, maximum dosage of zastaprazan in multiple administration (40 mg once‐daily) increased mean serum gastrin level to 211.4 pg/mL (SD 89.7) after 1 week, which was comparable to esomeprazole (253.1 ± 170.3 pg/mL; Table 1). 9 …”
Section: P‐cab Serum Gastrin Elevationmentioning
confidence: 99%
“…Declaration of personal interests : The authors' declarations of personal and financial interests are unchanged from those in the original article 9 …”
Section: Acknowledgementsmentioning
confidence: 99%